Os efeitos da modulação hemisférica nas assimetrias manuais: inibição inter-hemisférica e aumento da excitabilidade hemisférica - Lidiane Aparecida Fernandes (2016)
Performance asymmetry is characterized by the difference in the control of homologous contralateral body segments, expressed in different aspects of motricity. The differences in the performance of hands have been attributed to the contralateral hemisphere specialization in organization and control of voluntary movement. The hemispherical modulation may affect the electrical conductivity of the corpus callosum fiber between the hemispheres, resulting in increased or decreased inter-hemispheric communication and, consequently, reduction or increase of manual asymmetries. Thus, this study aimed to investigate the effects of inter-hemispheric inhibition and increased excitability in hemispheric asymmetries in a manual aiming task as well as analyze the control mechanisms associated with the changes in manual asymmetries. In the first experiment, the effects of inter-hemispheric inhibition (IHI) were investigated. Eleven male volunteers performed a manual pointing task. The volunteers participated in three sessions under different conditions: Dominant Hemisphere Inhibition (DHI); non-Dominant Hemisphere inhibition (NDHI) and Placebo (PL). Each session consisted of a pretest, followed by the specific condition of stimulation of the primary motor cortex (M1) and post-test for each hand. The sessions were separated by an interval of 48 hours. Experiment II aimed to investigate the effects of increased excitability hemispheric (EH) and analyze the control mechanisms associated with the change of manual asymmetries. Nine male volunteers performed a manual pointing task. This experiment followed the same design of the first experiment and consisted of three sessions: Excitability of non-Dominant Hemisphere (ENDH); Excitability of Dominant Hemisphere (EDH) and Placebo (PL). The results showed that hemispherical modulation modified manual asymmetries. IHI led to changes in performance and kinematic variables, while EH only affected relative time to peak velocity kinematic variable. Hemispheric modulation did not change the following variables: (1) peak velocity; (2) number of corrections in both experiments. The control mechanism associated with changes in asymmetries is the preprogramming of movement. In conclusion, hemispherical modulation was able to modify manual asymmetries, which is associated with longer times during the trajectory of motion controlled in a preprogrammed fashion, i.e., controlled centrally. The effects of hemispheric modulation were more evident for IHI and are in accordance with the propositions of hemispheric specialization. More studies are necessary to establish stronger links between biological handedness and manual asymmetries